APLIKASI POMPA HYDRAM UNTUK PENYEDIAAN AIR BERSIH DI DESA MENEMENG LOMBOK TENGAH - -, MULIADI; BONITA, MARETA KARLIN; RUWAIDAH, ELIZA (Buletin Udayana Mengabdi, 2015)
Shortage of cleanwater for domestic use, low levels of education, lack of jobs and welfare is a matter of general population in Indonesia. The aims of this community service is to raise the water from the Merocot’s fountain to settlements with applications of Hydraulic ram. The method used is applicable existing technologies and participation of the community in improving the standard of living welfare together. The results of this activity is that Merocot’s spring water, with ad is charge of 0.7liters/sec in the dry season and greater reach 2liters/sec during the rainy season, entered the shelter first and pumped with hydrant pump to higher ground by itself. Prototype hydrant pump output discharge 4.375liters/min, input pipe diameter 1inch, 3/4inch-diameter pipe output, out come pump 82 meters high, the amount of valve2 pieces, the slope of 65?installation, operation time of 24hours. Institutional SPAM village is managed by the communities themselves with the election of members’ democratic consensus. Administrators who will manage and take care of spam IbM results from the University of NTB. Society has the skills and soft skills to solve the drinking water problem in the future and another place. Preservation of the environment needs to be done in a way to make people aware of the importance of preserving the environment so that the springs are there now remain stable. Keywords: hydrampomp, energi terbarukan menemeng.